The Role of Leadership in Improving the Quality Management of Islamic Religious Education Learning in Schools - Muhammad Abi Hakkin Nazili; Siti Julaiha (Al-Qalam Institue, 2025)
Islamic Religious Education (PAI) plays a crucial role in shaping students' character and morality. This study aims to examine the role of Leadership in managing the quality of Islamic Religious Education (PAI) learning in schools to improve the quality of religious education. Issues include the lack of integration of Islamic values into learning and challenges with teachers' competency in using innovative methods. This study employed a descriptive, qualitative approach, including in-depth interviews, observation, and documentation. The results indicate that visionary, transformational, and exemplary Leadership play a significant role in creating a learning environment that supports the development of students' religious character. Effective Leadership integrates Islamic values into every aspect of learning, both academic and moral. The study concludes that Islamic value-based Leadership is efficacious in improving the quality of Islamic Religious Education (PAI) education by shaping students' religious character. This study enriches the theory of Islamic Religious Education Leadership by incorporating moral and spiritual dimensions into PAI quality management. Further research is recommended to examine the long-term impact of this Leadership.